2002
DOI: 10.4294/zisin1948.55.2_119
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Groundwater Level and Crustal Strain in and around the Kinki District Related to the 2001 Geiyo Earthquake

Abstract: Geological Survey of Japan made a groundwater observation network composed of 21 stations mainly along active faults in and around the Kinki district, which is a range of about 34-35.5°N and 134.5-136.7°E, for earthquake prediction research. These wells were newly made by Geological Survey of Japan after the 1995 Hyogo-ken Nanbu Earthquake (the Kobe Earthquake). Continuous observation at all the wells started in 1998. The 2001 Geiyo Earthquake (M6.7), occurred west off the network on Mar. 24, 2001. The depth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…5, which are KNM, OBK1, TNN, TKB3 and KWN-O. Koizumi et al (2002) presented a similar figure as Fig. 5 using data of the 2001 Geiyo earthquake, and discussed the relationship between the observed changes and the theoretical ones.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…5, which are KNM, OBK1, TNN, TKB3 and KWN-O. Koizumi et al (2002) presented a similar figure as Fig. 5 using data of the 2001 Geiyo earthquake, and discussed the relationship between the observed changes and the theoretical ones.…”
Section: Discussionsupporting
confidence: 63%
“…(2002) and Koizumi et al (2002) reported the groundwaterlevel changes and discussed relations between the changes and coseismic strain, respectively. The results show that groundwater-level responses in some wells are consistent with coseismic strain but that those in some wells are not.…”
Section: Introductionmentioning
confidence: 99%
“…3). This suggests that the changes in groundwater levels are qualitatively consistent with those of the volumetric strain (Koizumi et al 2002).…”
Section: Observation Sites Data and Methodssupporting
confidence: 65%
“…At KNG2, TYH1, and HTS, several previous postseismic changes in groundwater levels were mainly the same as the postseismic changes associated with the Sumatra earthquake (Tsukuda, 2000;Koizumi et al, 2002;Sato et al, 2005). In the case of the M7.1 and M7.4 off Kii peninsula earthquakes that occurred within 5 hours on September 5, 2004, postseismic groundwater level Table 3.…”
Section: Discussionmentioning
confidence: 80%